PENTINGNYA HAK ASASI MANUSIA (HAM) DALAM BERNEGARA - Hutabarat, Dany Try Hutama; Gumelar, Agung; Al Madina; Sari, Dina Puspita; Azhar, Khairul; Sinaga, Muhammad Sakha; Padila, Nurul; Azhari, Ridho; Simbolon, Santi Angriany; Khairani, Siti Miftha; Pratama, Yogi (Transpublika Publisher, 2022)
Human rights are a combination of natural rights that are universal, belong to every human being, and have been affixed to a person from birth as a direct gift or gift from God Almighty. Human rights must be upheld by every person, state, government, and law, especially in the context of the rule of law, which has become a characteristic of the rule of law in order to ensure the protection of human rights that have been enshrined in the constitutions and national laws of all legal states. Because, in a state of law, it highlights the existence of equality and equality before the law, without exception. As a result, the writing of this article is intended to see and deepen the phenomenon of human rights protection in the notion that leads to a rule of law, particularly in Indonesia, which is one of the world's rules of law countries. In order to obtain results and conclusions from the formulation of the problem, this article was created utilizing descriptive methods and data collecting through literature study.